Object Oriented Business Architecture on Online-exam and Assignment system - Basar, Erden; Haji-zada, Teymur (IEEE, 2014)
Business object architecture is a technology that was designed and developed during recent period. This architecture has a lot of benefits like scalability, flexibility and security. In business object architecture the logical architecture is separated into layers that give more scalability and reusability. The goal of this paper is implementing computer assisted examination system with business object architecture. The framework that is used for creating business objects is CSLA.NET
25th Annual Conference of the European-Association-for-Education-in-Electrical-and-Information-Engineering (EAEEIE) -- MAY 30-JUN 01, 2014 -- Cesme, TURKEY
Keywords: business object architecture; computer assisted exam system; assignment system; CSLA.NET